Legalitas Impor Vaksin Covid-19 Perspektif Maqashid Syariah - Allina Mustaufiatin Ni'mah; Syufa'at Syufa'at (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This article aims to determine the legality of importing Covid-19 vaccines by the Ministry of Health from sharia maqasid perspective. This article is a literature study using literature review as the primary legal source. The results of the study show that the legality of importing Covid-19 vaccines in maqshid sharia aims to make people believe and obey the government's vaccination program to decrease the spread of the Covid-19 virus and the death rate to protect the lives (hifáº“ al-nafs) of the Indonesian people. The legality of importing the Covid-19 vaccine using salam contract mechanism is known to have unfulfilled conditions, namely the object specification requirements.The object specifications in this case include halal assurance, thayib and safety guarantees of Covid-19 vaccine products. Therefore, the audit process from BPOM and halal certification from MUI used as the basis for the legality of importing the Covid-19 vaccine, make the object specification requirements fulfilled. If in the process of importing the Covid-19 vaccine there is force majeure, the agreement can be renewed or canceled and if there is a dispute, it can be resolved through arbitration.